Big gay wedding eaudiobook - Lane, Byron (Macmillan Audio, 2023)
This program is read by Noah Galvin, who starred in The Good Doctor , Dear Evan Hansen , The Real O'Neals , and Booksmart . An unashamedly proud, loud, and hilarious novel about a small town that's forever changed by a big gay wedding, perfect for fans of Red, White & Royal Blue and The Guncle Two grooms. One mother of a problem. Barnett Durang has a secret. No, not THAT secret. His widowed mother has long known he's gay. The secret is Barnett is getting married. At his mother's farm. In their small Louisiana town. She just doesn't know it yet. It'll be an intimate affair. Just two hundred or so of the most fabulous folks Barnett is shipping in from the "heathen coasts," as Mom likes to call them, turning her quiet rescue farm for misfit animals into a most unlikely wedding venue. But there are forces, both within this modern new family and in the town itself, that really don't want to see this handsome couple march down the aisle. It'll be the biggest, gayest event in the town's history if they can pull it off, and after a glitter-filled week, nothing will ever be the same. Big Gay Wedding is an uplifting audiobook about the power of family and the unconditional love of a mother for her son. A Macmillan Audio production from Henry Holt & Company.